Mapping knowledge structure and themes trends of biodegradable Mg-based alloy for orthopedic application: A comprehensive bibliometric analysis - Zheng, Zitian; Xu, Wennan; Xu, Yanan; Xue, Qingyun (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Since Lambotte and Payr first studied Mg-based alloys for orthopedics in 1900, the research of this field has finally ushered in vigorous development in the 21st century. From the perspective of quantitative analysis, this paper clearly demonstrated the global research trend from 2005 to 2021 by using bibliometrics and scientometric analysis. Methods: We obtained the publications from the Web of Science Core Collection (WoSCC) database. The bibliometric and scientometric analysis was conducted by using R software, CiteSpace software, VOSviewer software, Pajek software and Microsoft Excel program. Results: In total, 1921 publications were retrieved. It can be found that the number of publications is gradually increasing year by year. We can find that the most prolific countrie, institution and researcher are China, Chinese Academy of Sciences and Zheng Yufeng, respectively. The most influential journals in this field are Acta Biomaterialia and Biomaterials, with 16,511 and 12,314 total citations, respectively. By conducting the co-cited documents-based clustering analysis, 16 research hotspots and their representative studies have been identified. Besides, by conducting analysis of keywords, we divided the keyword citation bursts representing the development of the field into three stages. Conclusion: The number of researches on the biodegradable Mg-based alloys increased sharply all over the world in the 21st century. China has made significant progress in biodegradable Mg-based alloy research. More focus will be placed on osteogenic differentiation, fabrication, graphene oxide, antibacterial property, bioactive glass and nanocomposite, which may be the next popular topics in the field.